Low-temperature thermal transport measurements of oxygen-annealed Yb2Ti2O7 - Toews, WH; Reid, JA; Thompson, JD; Prabhakaran, D; Coldea, R; Hill, RW (American Physical Society, 2020)
Low-temperature thermal conductivity measurements have been conducted on an oxygen-annealed single crystal of Yb2Ti2O7 from 60 mK to 50 K and in magnetic fields up to 8 T applied in the [111] crystallographic direction. The temperature dependence of the conductivity in zero field shows a significant peak in thermal conductivity at T∼13 K and a sharp anomaly at Tc∼0.2 K suggesting that the sample's behavior is representative of the high-purity limit, with low levels of disorder. The magnetic field dependence of the thermal conductivity close to Tc reveals a reentrant magnetic phase for a field in the [111] direction. With this information, analysis of the very low magnetic field behavior of the thermal conductivity suggests the presence of significant fluctuations close to the phase line.